Exploração da popularidade para busca de informação em blogs - Luiz Guilherme Pais dos Santos (2009)
The blogosphere is a highly dynamic and interconnected subset of the Web that has triggered a lot of interest due to its social and personal nature. In this dissertation, we present a study of an important social aspect of these blogs, namely popularity. The most popular blogs from four important blog domains in Brazil were crawled for a considerable period of time in order to collect information about the most popular blogs. The experiments, conducted with several volunteers, show that despite the blogosphere being a social network, popularity has been underexplored by at least the most popular search engines in the context of blog search. In the experiments, queries specifically formulated for retrieving these popular blogs were not capable of ranking them in the top positions (top 100) of the most popular search engines, and their page ranks, as measured by the typical web graph topology of links, are very low. It is also shown that explicitly incorporating popularity in the search engine algorithm produces rankings which were considered by volunteers, in general, very relevant.